Streptococcus dysgalactiae From Farm‐Raised Channel Catfish in Mississippi, USA, With Notes on Fish‐Associated Group C S. dysgalactiae - Sujita Balami; Lester H. Khoo; Caitlin E. Older; Geoffrey C. Waldbieser; Alvin C. Camus; Taylor I. Heckman; Cynthia C. Ware; Bradley M. Richardson; John P. Hawke; Adrián López‐Porras; Esteban Soto; Craig A. Shoemaker; et al. (Journal of Fish Diseases, 2025)
Lancefield serological group C Streptococcus dysgalactiae (GCSD) is an emerging cause of fish disease worldwide, largely associated with mariculture in Asia. In the United States (US), GCSD had been a pathogen of minimal concern for fish, but recent cases indicate a putative emergence in wild and cultured freshwater fish populations in the Americas. The current study discusses three novel cases of GCSD‐associated streptococcosis in US farm‐raised channel catfish ( Ictalurus punctatus ) occurring in Mississippi, US, in 2022 and 2023. Infected fish presented with pendulous abdomens, red swollen vents, and petechiae on the mouth, fins and ventral lateral abdomen. Clinical isolates were cultured from the kidney and brain and initially confirmed as GCSD by 16S rRNA gene sequencing, followed by phylogenetic analyses using the superoxide dismutase gene ( sod A), 16S/23S internal transcribed spacer region and nine genes within a multilocus sequence analysis scheme for piscine pathogenic Streptococcus . Catfish GCSD were highly homologous to fish strains from published reports from Asia and South America, forming a discrete phylogenetic clade, separate from human and other terrestrial animal isolates. Pairwise genomic comparisons suggest this fish‐associated group does not belong to any currently recognised subspecies and may represent a unique subtype. The broadening host and geographic range of GCSD, coupled with the evidence of a discrete aquatic lineage and recent reports from freshwater fishes in the southeastern US, suggest GCSD is a potential emergent threat to catfish aquaculture in the US.

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Valorisation potential of low-grade fly ash as a sustainable MgO source for iron ore sintering: Insights from in situ X-ray diffraction and tablet studies - Kenji Taira; Nathan A.S. Webster; Isis R. Ignácio; Natalie Ware; Anita M. D’Angelo; Lian Zhang; Mark I. Pownceby (Journal of Environmental Chemical Engineering, 2024)

Zinc on the edge—isotopic and geophysical evidence that cratonic edges control world-class shale-hosted zinc-lead deposits - David L. Huston; David C. Champion; Karol Czarnota; Jingming Duan; Matthew Hutchens; Suzanne Paradis; Mark Hoggard; Bryant Ware; George M. Gibson; Michael P. Doublier; Karen Kelley; Anne McCafferty; et al. (Mineralium Deposita, 2023)
The North Australian Zinc Belt is the largest zinc-lead province in the world, containing three of the ten largest known individual deposits (HYC, Hilton-George Fisher, and Mount Isa). The Northern Cordillera in North America is the second largest zinc-lead province, containing a further two of the world’s top ten deposits (Red Dog and Howards Pass). Despite this world-class endowment, exploration in both mineral provinces during the past 2 decades has not been particularly successful, yielding only two significant discoveries (Teena, Australia, and Boundary, Canada). One of the most important aspects of exploration is to choose mineral provinces and districts within geological belts that have the greatest potential for discovery. Here, we present results from these two zinc belts that highlight previously unused datasets for area selection and targeting. Lead isotope mapping using analyses of mineralized material has identified gradients in μ ( 238 U/ 204 Pb) that coincide closely with many major deposits. Locations of these deposits also coincide with a gradient in the depth of the lithosphere-asthenosphere boundary determined from calibrated surface wave tomography models converted to temperature. Furthermore, gradients in upward-continued gravity anomalies and a step in Moho depth correspond to a pre-existing major crustal boundary in both zinc belts. A spatial association of deposits with a linear mid- to lower-crustal resistivity anomaly from magnetotelluric data is also observed in the North Australian Zinc Belt. The change from thicker to thinner lithosphere is interpreted to localize prospective basins for zinc-lead mineralization and to control the gradient in lead isotope and geophysical data. These data, when combined with data indicative of paleoenvironment and changes in plate motion at the time of mineralization, provide new exploration criteria that can be used to identify prospective mineralized basins and define the most favorable parts of these basins.

Evaluation of Edwardsiella piscicida basS and basR mutants as vaccine candidates in catfish against edwardsiellosis - Mohamed Sayed; Matt Griffin; Cynthia Ware; Ozan Ozdemir; Hasan C. Tekedar; Manal Essa; Attila Karsi; Mark L. Lawrence; Hossam Abdelhamed (Journal of Fish Diseases, 2022)
Catfish farming is the largest aquaculture industry in the United States and an important economic driver in several southeastern states. Edwardsiella piscicida is a Gram‐negative pathogen associated with significant losses in catfish aquaculture. Several Gram‐negative bacteria use the BasS/BasR two‐component system (TCS) to adapt to environmental changes and the host immune system. Currently, the role of BasS/BasR system in E. piscicida virulence has not been characterized. In the present study, two mutants were constructed by deleting the basS and basR genes in E. piscicida strain C07‐087. Both mutant strains were characterized for virulence and immune protection in catfish hosts. The Ep Δ basS and Ep Δ basR mutants were more sensitive to acidic environments and produced significantly less biofilm than the wild‐type. In vivo studies in channel catfish ( Ictalurus punctatus ) revealed that both Ep Δ basS and Ep Δ basR were significantly attenuated compared with the parental wild‐type (3.57% and 4.17% vs. 49.16% mortalities). Moreover, there was significant protection, 95.2% and 92.3% relative percent survival (RPS), in channel catfish vaccinated with Ep Δ basS and Ep Δ basR against E. piscicida infection. Protection in channel catfish was associated with a significantly higher level of antibodies and upregulation of immune‐related genes (IgM, IL‐8 and CD8‐α) in channel catfish vaccinated with Ep Δ basS and Ep Δ basR strains compared with non‐vaccinated fish. Hybrid catfish (channel catfish ♀ × blue catfish ♂) challenges demonstrated long‐term protection against subsequent challenges with E. piscicida and E. ictaluri. Our findings demonstrate BasS and BasR contribute to acid tolerance and biofilm formation, which may facilitate E. piscicida survival in harsh environments. Further, our results show that Ep Δ basS and Ep Δ basR mutants were safe and protective in channel catfish fingerlings, although their virulence and efficacy in hybrid catfish warrant further investigation. These data provide information regarding an important mechanism of E. piscicida virulence, and it suggests Ep Δ basS and Ep Δ basR strains have potential as vaccines against this emergent catfish pathogen.

Pharmacokinetics of cannabichromene in a medical cannabis product also containing cannabidiol and Δ9-tetrahydrocannabinol: a pilot study - Erica N. Peters; Laura MacNair; Irina Mosesova; Uwe Christians; Cristina Sempio; Jost Klawitter; M. Hunter Land; Mark A. Ware; Cynthia Turcotte; Marcel O. Bonn-Miller (European Journal of Clinical Pharmacology, 2022)
Purpose Cannabichromene (CBC) is a phytocannabinoid commonly found in cannabis, yet its acute post-dose pharmacokinetics (PK) have not been examined in humans. This is a secondary data analysis from a trial investigating Spectrum Yellow oil, an oral cannabis product used for medical purposes that contained 20 mg cannabidiol (CBD), 0.9 mg Δ 9 -tetrahydrocannabinol (THC), and 1.1 mg CBC, per 1 mL of oil. Methods Participants ( N = 43) were randomized to one of 5 groups: 120 mg CBD, 5.4 mg THC, and 6.6 mg CBC daily; 240 mg CBD, 10.8 mg THC, and 13.2 mg CBC daily; 360 mg CBD, 16.2 mg THC, and 19.8 mg CBC daily; 480 mg CBD, 21.6 mg THC, and 26.4 mg CBC daily; or placebo. Study medication was administered every 12 h for 7 days. Plasma CBC concentrations were analyzed by a validated two-dimensional high-performance liquid chromatography–tandem mass spectrometry assay. Results After a single dose and after the final dose, the C max of CBC increased by 1.3–1.8-fold for each twofold increase in dose; the t max range was 1.6–4.3 h. Based on the ratio of administered CBD, THC, and CBC to the plasma concentration, the dose of CBD was 18 times higher than the dose of CBC, yet the AUC 0– t of CBD was only 6.6–9.8-fold higher than the AUC 0– t of CBC; the dose of THC was similar to the dose of CBC, yet THC was quantifiable in fewer plasma samples than was CBC. Conclusions CBC may have preferential absorption over CBD and THC when administered together. Trial Registration : Australian New Zealand Clinical Trials Registry #ACTRN12619001450101, registered 18 October 2019.

Anti-drug Antibody Validation Testing and Reporting Harmonization - Heather Myler; João Pedras-Vasconcelos; Kelli Phillips; Charles Scott Hottenstein; Paul Chamberlain; Viswanath Devanaryan; Carol Gleason; Joanne Goodman; Marta Starcevic Manning; Shobha Purushothama; Susan Richards; Honglue Shen; et al. (The AAPS Journal, 2022)
Evolving immunogenicity assay performance expectations and a lack of harmonized anti-drug antibody validation testing and reporting tools have resulted in significant time spent by health authorities and sponsors on resolving filing queries. Following debate at the American Association of Pharmaceutical Sciences National Biotechnology Conference, a group was formed to address these gaps. Over the last 3 years, 44 members from 29 organizations (including 5 members from Europe and 10 members from FDA) discussed gaps in understanding immunogenicity assay requirements and have developed harmonization tools for use by industry scientists to facilitate filings to health authorities. Herein, this team provides testing and reporting strategies and tools for the following assessments: (1) pre-study validation cut point; (2) in-study cut points, including procedures for applying cut points to mixed populations; (3) system suitability control criteria for in-study plate acceptance; (4) assay sensitivity, including the selection of an appropriate low positive control; (5) specificity, including drug and target tolerance; (6) sample stability that reflects sample storage and handling conditions; (7) assay selectivity to matrix components, including hemolytic, lipemic, and disease state matrices; (8) domain specificity for multi-domain therapeutics; (9) and minimum required dilution and extraction-based sample processing for titer reporting. Graphical Abstract

A prospective observational study of problematic oral cannabinoid use - Mark A. Ware; Marc O. Martel; Roman Jovey; Mary E. Lynch; Joel Singer (Psychopharmacology, 2018)

Current Trends in Ligand Binding Real-Time Measurement Technologies - Stephanie Fraser; Judy Y. Shih; Mark Ware; Edward O’Connor; Mark J. Cameron; Martin Schwickart; Xuemei Zhao; Karin Regnstrom (The AAPS Journal, 2017)

Cannabinoids for the Treatment of Chronic Non-Cancer Pain: An Updated Systematic Review of Randomized Controlled Trials - M. E. Lynch; Mark A. Ware (Journal of Neuroimmune Pharmacology, 2015)

Characterization of Endocarp Biomass and Extracted Lignin Using Pyrolysis and Spectroscopic Methods - Anne E. Harman-Ware; Mark Crocker; Robert B. Pace; Andrew Placido; Samuel Morton; Seth DeBolt (BioEnergy Research, 2015)

The Use of Betaine HCl to Enhance Dasatinib Absorption in Healthy Volunteers with Rabeprazole-Induced Hypochlorhydria - Marc R. Yago; Adam Frymoyer; Leslie Z. Benet; Gillian S. Smelick; Lynda A. Frassetto; Xiao Ding; Brian Dean; Laurent Salphati; Nageshwar Budha; Jin Y. Jin; Mark J. Dresser; Joseph A. Ware (The AAPS Journal, 2014)

Next Generation Ligand Binding Assays—Review of Emerging Real-Time Measurement Technologies - Stephanie Fraser; Mark Cameron; Edward O’Connor; Martin Schwickart; Michael Tanen; Mark Ware (The AAPS Journal, 2014)

Schematic maps in MobileGIS environments: an automated simulated annealing based case study - Suchith Anand; J. Mark Ware; Sarah Sharples; Mike Jackson; Jim Nixon (Cognitive Processing, 2006)